2017
DOI: 10.1038/ijo.2017.255
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with circulating concentrations of irisin in the general population cohort of the ABCD study

Abstract: Our study confirms, in a cohort of a general population, that irisin concentrations gradually increase with the usual level of habitual physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 55 publications
2
31
2
Order By: Relevance
“…A population-based cohort included 967 non-diabetic people living in Germany [32], this study investigated the association between irisin and lipid levels, finding a significant association with favorable lipid profile; in particular, an inverse association of irisin with total cholesterol concentration. Buscemi S, et al also found a positive association between HDL-cholesterol concentrations and irisin concentration [33]. However, we found a positive association between irisin and triglycerides, no association with total cholesterol or HDL-C.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…A population-based cohort included 967 non-diabetic people living in Germany [32], this study investigated the association between irisin and lipid levels, finding a significant association with favorable lipid profile; in particular, an inverse association of irisin with total cholesterol concentration. Buscemi S, et al also found a positive association between HDL-cholesterol concentrations and irisin concentration [33]. However, we found a positive association between irisin and triglycerides, no association with total cholesterol or HDL-C.…”
Section: Discussioncontrasting
confidence: 65%
“…So the conclusion should only be generalized to overweight rather than different grade of obesity. Moreover, there has been controversies regarding available irisin ELISA kits, including antibody specificity of antibody, its cross-reactivity with FNDC5 and the wide range of irisin levels between different studies [33] [35]. In addition, different ethnicity and lifestyle may have different results; generalization beyond Asian populations should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…In order to promote the participation of people of a younger age with no known cardiovascular, liver, metabolic or nutritional diseases, an echographic check of the thyroid was also proposed to the customers of the mall. The demographic characteristics of the ABCD cohort were similar to, even non‐overlapping with, those of the general population of the same range of age (18‐90 years) living in Palermo in 2011, as presented elsewhere and in Table . The original cohort was re‐contacted (telephone, e‐mail, letter) in 2015, and those who agreed to participate in the study were asked to come to the Metabolism and Clinical Nutrition Laboratory of the Department of Internal and Specialized Medicine at the University of Palermo, and were re‐examined from March 21th to July 31th.…”
Section: Methodsmentioning
confidence: 58%
“…The relationship between irisin level and chronic exercise training or habitual physical activity is controversial [31]: both increasing [1,32] and decreasing [4,33] circulating irisin concentrations have been observed. In agreement with the results of the KarMeN study, that correlated irisin concentrations with both subjective and objective measures of physical activity in healthy, normal weight subjects [34], we found no association between irisin and habitual physical activity in our patients examined under resting condition.…”
Section: Discussionmentioning
confidence: 99%